Democracy as an equilibrium: rational choice and formal political theory in democratization research. Issue 1 (2nd January 2019) - Svolik, Milan W.
ABSTRACT: Over the past quarter century, some of the most influential propositions about democratization have been developed with the tools of rational choice and formal political theory. In this article, I assess the contribution of this research paradigm to the study of democratization. Substantively, formal theorists have examined two sets of underlying mechanisms. The first conceives of elections as a solution to and a source of commitment problems; the second emphasizes the conflict-reducing properties of democratic institutions. A distinguishing feature of both mechanisms is that democracy does not emerge as an end in itself, but rather because democracy reduces political and economic transaction costs, major sources of which are asymmetries of information, commitment problems, and violence. Methodologically, formal-theoretic research contributes to the development of analytically transparent, reproducible theoretical arguments and facilitates the communication and accumulation of knowledge, both within political science and across disciplines. Finally, by demanding an explicit statement of microfoundations and by focusing on the consequences of strategic interactions, formal-theoretical research helps democratization scholars to assess external validity limitations, anticipate general equilibrium critiques, and curb the temptation to fish for statistical significance.